Spatial Designs on Metamaterial Sensors for Enhancing Signals and Detecting Extracellular Vesicles - Derin, Esma; Yilmaz, Eylul Gulsen; Erdem, Ozgecan; Aslan, Yusuf; Kafadenk, Abdullah; Celik, Suleyman; Inci, Fatih (Amer Chemical Soc, 2025)
Biosensors, while holding immense promise for biomarker detection, face substantial challenges in analytical performance, fabrication intricacies, and complex applications, hindering their seamless integration into point-of-care (POC) settings. Metamaterial-based plasmonic biosensors offer tremendous potential for biomarker detection; however, their widespread adoption in POC diagnostics remains hampered by limitations in sensitivity, fabrication complexity, and production cost. Herein, we introduce, for the first time, in situ-controlled spatial designs on metamaterial-based plasmonic sensors, demonstrating unprecedented sensitivity in detecting extracellular vesicles (EVs). In the fabrication process, commercially available optical disks were repurposed as nanostructured substrates, yielding a cost reduction of up to 260-fold ($0.90 per sensor) and a fabrication time reduction of approximately 960-fold, compared to conventional e-beam lithography. Leveraging inherent nanogratings, measurements are conducted on a compact, palm-sized platform, addressing challenges in usability and portability associated with bulky optical designs. Through ex situ immobilization of gold nanoparticles (AuNPs) or in situ formation of nanoislands (NIs), we have engineered plasmonic hotspots that substantially enhanced local electric field intensities, thereby amplifying the bulk refractive index sensitivity of the sensors. Finite-difference time-domain simulations confirmed that the spatial arrangement and interparticle distances of spatial designs enhance near-field effects. The optimized platform exhibits up to a 5.5-fold enhancement in refractive index sensitivity. Moreover, based on data obtained from nanoparticle tracking analysis (NTA), fluorescence-enhanced NTA (fNTA), and recent literature benchmarks, the platform demonstrated detection limits of 104 particles/mu L (as determined by raw NTA measurements), approximately 330 fg/mu L (estimated via literature-based EV mass calculations), and 138 EVs/mu L (quantified via fNTA using marker-specific labeling). Herein, we anticipate that repurposing disks as metamaterial sensors has the potential to address pressing challenges in usability, portability, cost, and complexity. Besides, 3D configurations on sensors would improve the analytical performance, offering highly sensitive and facile platforms for diverse applications in the future.
Keywords: metamaterial sensors; optical disks; nanoislands; extracellular vesicles; signal enhancement